Examining English Reading Comprehension Skills Among Junior High School Students: The Influence of School Values And Gender - Carolina Lupi Hidayati; Chuzaimah Dahlan Diem; Mulyadi Eko Purnomo; Izzah Izzah (STAI Hubbulwathan Duri, 2025)
Reading comprehension is a crucial skill that supports the academic success of junior high school students, particularly in an increasingly globalized world. Understanding students' proficiency in this area is essential for developing effective teaching strategies. This quantitative descriptive study evaluated the English reading comprehension abilities of 80 ninth-grade students at MTs Muqimus Sunnah. The assessment was based on an 18-question reading comprehension test covering four key aspects: contraction, sequence, vocabulary, and inference. The study also analyzed performance differences by gender and grade level. The results revealed that female students scored higher on average (4.43) than male students (3.66), though the difference was not statistically significant. Students demonstrated the strongest performance in contraction (8.68) and sequence (7.73) items. However, they struggled with context understanding and inference, indicating a need for improvement in higher-order reading skills. The findings suggest that while students show proficiency in recognizing structural and sequential elements, they face challenges in deeper analytical reading. This highlights the importance of targeted instructional strategies that emphasize vocabulary development and critical reading skills. This study provides valuable insights for educators and policymakers in enhancing English literacy instruction. Structured interventions focusing on analytical comprehension and vocabulary acquisition are recommended to address observed weaknesses and support overall reading development.